Comparison of the Effectiveness between Oral NSAIDs and Dextrose Prolotherapy in Knee Osteoarthritis - Sugiyanta, Sugiyanta; Dwicahyandari, Winie Septhia; Efendi, Erfan; Wisudanti, Desie Dwi (Universitas Islam Bandung, 2023)
Non-steroidal anti-inflammatory drugs (NSAIDs) are the first treatment choice for pain relief in osteoarthritis (OA). However, known to have an 85% risk of side effects on the gastrointestinal and a 40% chance of cardiovascular complications. In addition, in certain classes of NSAIDs, the risk of chronic kidney disease increases due to long-term consumption. On the other hand, dextrose prolotherapy is a regenerative therapy. This study aimed to compare the effectiveness of oral NSAIDs with dextrose prolotherapy in knee OA based on clinical features. This study used an observational method (cross-sectional) conducted in three locations; Jember Clinic Hospital, Balung Hospital, and Harapan Mulya Kertonegoro Jenggawah Clinic from September 2021 to March 2022. Of the 75 population, 23 patients with mild to moderate knee OA were divided into two groups; 15 samples of dextrose prolotherapy and eight samples of oral NSAIDs. Data in the study showed the mean WOMAC score in the dextrose prolotherapy group was 12.4±11.7, while the oral NSAID group was 34.75±17.6. A total of 14 samples experienced a decrease in scores after switching from oral NSAIDs to dextrose prolotherapy. Bivariate analyses were performed using Mann-Whitney and Wilcoxon tests. Both statistical tests show a p=0.001 (p<0.05). Thus, this study concluded that dextrose prolotherapy was more effective than oral NSAIDs in knee OA.